Effectiveness of a cognitive-behavior therapy protocol for posttraumatic stress disorder and implications for trauma memory narratives - Mello, Patricia Gaspar (2014)
Posttraumatic Stress Disorder (PTSD) is a mental disorder developed after the exposure to a traumatic event. People suffering from PTSD usually presents symptoms of reexperiencing, avoidance, hyperarousal, shame, and guilty. Several theories try to explain how PTSD is developed, but there is relative consensus about the influence of an impaired memory processing. Literature points out many types of treatments that aim to regulate this memory impairment and, therefore, reduce PTSD symptoms. Cognitive-Behavior Therapy (CBT) is considered a gold-standard treatment for PTSD. However, most studies about CBT for PTSD are developed in the military context or in developed countries. As far as we know, there is a limited number of studies exploring this subject in Brazil, even with evidence suggesting Brazilian CBT therapists have different treatment approaches when compared with American CBT therapists. Our study aimed to verify the efficacy of an adapted CBT treatment for PTSD in Brazilians regarding PTSD symptoms, cognitions, depression and trauma memory content. This dissertation is composed by (1) a brief introduction, explaining the main concepts we used to develop the study; (2) a theoretical section composed by a systematic review about CBT techniques for PTSD treatment; (3) an empirical section composed by two papers, being one regarding the efficacy of adapted CBT protocol for PTSD symptoms, cognitions and depression, another about memory content in PTSD before and after exposure tasks; and (4) final considerations summarizing our main findings. Results show that our CBT protocol successfully reduces PTSD symptomatology, patient s memory seems to be less fragmented and they tend to include less psychophysiological sensations of fear and anxiety in their trauma memory narratives after therapy. The results suggest our CBT protocol is effective on the treatment of PTSD in Brazilians and it helps patients to organize and attribute a more functional meaning to their traumatic experiences.